Development of low glycemic index cookies made from functional cassava pulp flour - Hidayat, Beni; Hasanudin, Udin; Siti Nurdjanah,; Yuliana, Neti; Zukryandry, (Penerbit Universiti Kebangsaan Malaysia, 2023)
One of the food ingredients with the potential to be used as raw material for low glycemic index food is functional cassava pulp flour (FCPF) which has a dietary fiber content of 23.84% and resistant starch of 7.31%. The present research aimed to obtain the optimal substitution concentration of FCPF to produce cookies with the best nutritional, organoleptic, and physical characteristics and a low glycemic index. It was arranged in a Completely Randomized Design (CRD) with six levels of substitution concentration of FCPF, namely, 0% (control), 10%, 20%, 30%, 40%, and 50%. The results showed that the higher the concentration of FCPF substitution, the higher the fiber content, the resistant starch content, and the texture of cookies. Cookies with a 50% FCPF substitute concentration have the same organoleptic quality as those made from wheat flour (6.6 versus 6.9) but with the lowest glycemic index (40.29%). Cookie products with a 50% FCPF formulation are categorized as foods with a low glycemic index.